2021
DOI: 10.1021/acs.joc.1c00923
|View full text |Cite
|
Sign up to set email alerts
|

Directing Group Enables Electrochemical Selectively Meta-Bromination of Pyridines under Mild Conditions

Abstract: Without the use of catalysts and oxidants, a facile and sustainable electrochemical bromination protocol was developed. By introducing the directing groups, the regioselectivity of pyridine derivatives could be controlled at the meta-position utilizing the inexpensive and safe bromine salts at room temperature. A variety of brominated pyridine derivatives were obtained in 28–95% yields, and the reaction could be readily performed at a gram scale. By combining the installation and removing the directing group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…Based on the above results and previous reports ( Yuan et al, 2019 ; Gou et al, 2021 ; Wu et al, 2021 ), a plausible reaction mechanism for the electrochemical bromination of glycals was depicted in Scheme 4 . A bromine anion was oxidized to the bromine radical on the anode and subsequently molecular Br 2 .…”
Section: Resultssupporting
confidence: 63%
“…Based on the above results and previous reports ( Yuan et al, 2019 ; Gou et al, 2021 ; Wu et al, 2021 ), a plausible reaction mechanism for the electrochemical bromination of glycals was depicted in Scheme 4 . A bromine anion was oxidized to the bromine radical on the anode and subsequently molecular Br 2 .…”
Section: Resultssupporting
confidence: 63%
“…Steady-state photolysis of PTH and TBACl was performed in the presence of a halogen atom trap, 1,1-diphenylethene (DPE). , Continuous irradiation with 390 and 532 nm light through two sides of the sample yielded the photoproduct where one chlorine atom was added to DPE, identified by gas chromatography–mass spectrometry (GC–MS) (Figure S7). Control experiments indicated that irradiation with exclusively 390 nm light generated some chlorine-substituted DPE but with a significantly diminished yield, which is consistent with trace chlorine-atom formation from the aforementioned disproportionation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the potential application prospects of Ce catalysts and in continuation of our interest in the generation of heteroatom radicals (Cl·, , Br·, , and N· ) via a sustainable approach, we envisioned to replace the chemical oxidants with traceless electricity to enable the LMCT of Ce IV providing the Cl· species. Hence, a sustainable photoelectrochemical CeCl 3 -mediated protocol to construct the α,α-dichloroketones from aryl acetylenes was established (Scheme d).…”
Section: Introductionmentioning
confidence: 99%